Making Public Procurement Work for Women - International Trade Centre (United Nations, 2021)
In developed countries, public procurement accounts for almost 15% of gross domestic product; in some developing countries, this figure can reach as high as 40%. It is shocking that women-owned businesses account for a mere 1% of this critical sector. Women-owned businesses often cite lack of information about opportunities and requirements, complex procedures, and strict financial and qualification requirements as barriers to winning public tenders. This publication guides policymakers, procurement officers and other stakeholders on ways that they can contribute to improving women’s participation in public procurement. It provides a step-by-step guide to assess the state of their inclusion in public procurement, to identify barriers that women face, to understand policy options and procurement opportunities, to design a roadmap, and to monitor progress over time. It also features case studies from three countries at the forefront of this initiative – Chile, the Gambia and Nigeria – which are all finding solutions to these challenges.